Dissolving long-term romantic relationships: Assessing the role of the social context. (May 2013) - Hogerbrugge, Martijn J. A.; Komter, Aafke E.; Scheepers, Peer
Previous research on the dissolution of long-term romantic relationships has mostly focused on determinants that reflect either the characteristics of the individual partners or the characteristics of the relationship itself. The role of the social context in which couples are embedded has received less attention. This study assesses the association between three characteristics of the social context and the dissolution of long-term romantic relationships simultaneously: the prevalence of divorce in the network of the couple, the extent to which the networks of partners overlap each other, and the amount of social capital in the network of the couple. Using nationally representative panel data from the first and second waves of the Netherlands Kinship Panel Study, partial support was found for the link between the prevalence of divorce and network overlap on the one hand, and the likelihood to dissolve long-term romantic relationships on the other hand, among a sample of 3406 married and 648 unmarried cohabiting respondents. The association with social capital was found to differ between married and unmarried cohabiting respondents, as well as to depend upon the type of relationship the social capital is based in. These findings were interpreted to reflect differences in the symbolic meanings of marital and cohabiting relationships, and differences in types of social capital to which a person has access: relationship-specific versus non-relationship-specific social capital, with the former potentially impeding dissolution, and the latter potentially acting as an alternative to the relationship, thereby encouraging dissolution.